VELOCITY FIELD COMPUTATION IN VIBRATED GRANULAR MEDIA USING AN OPTICAL FLOW BASED MULTISCALE IMAGE ANALYSIS METHOD - Debayle, Johan; Raihane, Ahmed; Belhaoua, Abdelkrim; Bonnefoy, Olivier; Thomas, Gérard; Chaix, Jean-Marc; Pinoli, Jean-Charles (Image Analysis and Stereology, 2011)
An image analysis method has been developed in order to compute the velocity field of a granular medium (sand grains, mean diameter 600 μm) submitted to different kinds of mechanical stresses. The differential method based on optical flow conservation consists in describing a dense motion field with vectors associated to each pixel. A multiscale, coarse-to-fine, analytical approach through tailor sized windows yields the best compromise between accuracy and robustness of the results, while enabling an acceptable computation time. The corresponding algorithmis presented and its validation discussed through different tests. The results of the validation tests of the proposed approach show that the method is satisfactory when attributing specific values to parameters in association with the size of the image analysis window. An application in the case of vibrated sand has been studied. An instrumented laboratory device provides sinusoidal vibrations and enables external optical observations of sand motion in 3D transparent boxes. At 50 Hz, by increasing the relative acceleration G, the onset and development of two convective rolls can be observed. An ultra fast camera records the grain avalanches, and several pairs of images are analysed by the proposed method. The vertical velocity profiles are deduced and allow to precisely quantify the dimensions of the fluidized region as a function of G.